(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Direct Oral Anticoagulants (DOACs), represented by dabigatran, apixaban, rivaroxaban, and edoxaban, are widely used in the treatment of venous thromboembolism and the prevention of embolic events associated with atrial fibrillation. This article addresses the applicability of these medications in these conditions as well as in other clinical situations. Objective: To review the use of direct oral anticoagulants in deep vein thrombosis and discuss their growing application in cardiovascular prevention and the management of claudication, analyzing benefits and limitations in different clinical groups. Methods: Literature review of selected articles from PubMed and Clinical Guidelines. Results: DOACs have become the mainstay in the treatment of venous thromboembolism, enabling outpatient management of many of these cases from diagnosis. Their applicability extends to oncology patients with thrombosis, orthopedic surgical prophylaxis, cardiovascular prevention, and peripheral arterial disease. Despite the need for dose adjustments in special groups, such as chronic kidney disease patients, and restrictions in populations like pregnant women, lactating women, those with antiphospholipid syndrome, or dialysis patients, these medications have gained increasing clinical relevance. Conclusion: Since their approval, DOACs have gained popularity. In addition to treating deep vein thrombosis, they can be used for cardiovascular prevention and the symptomatic relief of intermittent claudication. However, the need for further studies remains to expand their safety and application in specific patient groups.